Pengukuran Kinerja Keuangan Pada Bank Umum Syariah Menggunakan Indikator Kinerja Perbankan Syariah - Carmidah Carmidah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
This study aims to determine the effect of measuring financial performance using financial ratios of Capital Adequacy, Liquidity, on the profitability of Islamic Commercial Banks as measured by Return On Assets (ROA). The population and sample of this research are all Islamic Commercial Banks in Indonesia as many as 14 Islamic Commercial Banks selected by the Purposive Sampling method. The data analysis technique used multiple regression analysis method with panel data. The results of this study indicate that partially and simultaneously there is an influence between Capital Adequacy Ratio, Liquidity (Financing to Deposit Ratio), asset quality (Non Performing Financing) and Operational Cost Efficiency of Operating Income (BOPO) on the disclosure of Profitability in Commercial Banks Sharia in Indonesia..